Analysis of Calculation of Production Costs and Operational Costs Against Sales Results of PT. Indofood Sukses Makmur, Tbk. 2017-2019 period: Analisis Perhitungan Biaya Produksi Dan Biaya Operasional Terhadap Hasil Penjualan PT. Indofood Sukses Makmur, Tbk. Periode 2017-2019 - Salsabillah, Savira; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the analysis of the calculation of production costs and operating costs on the sales of PT. Indofood Sukses Makmur, Tbk. 2017-2019 period. This research method is a qualitative method. The object of this research is the company PT. Indofood. Tbk period 2017-2019. The data used is secondary data. Proceeds from the sale of PT. Indofood, Tbk. The 2017-2019 period has increased every year. This is due to the factors of production costs and operational costs. Sales can be said to be successful if a company is able to issue a budget that is in production costs such as raw material costs, direct labor costs and factory overhead costs.